2017
DOI: 10.1074/jbc.m116.764357
|View full text |Cite
|
Sign up to set email alerts
|

Rapid regulation of sialidase activity in response to neural activity and sialic acid removal during memory processing in rat hippocampus

Abstract: Sialidase cleaves sialic acids on the extracellular cell surface as well as inside the cell and is necessary for normal long-term potentiation (LTP) at mossy fiber-CA3 pyramidal cell synapses and for hippocampus-dependent spatial memory. Here, we investigated in detail the role of sialidase in memory processing. Sialidase activity measured with 4-methylumbelliferyl-α-d--acetylneuraminic acid (4MU-Neu5Ac) or 5-bromo-4-chloroindol-3-yl-α-d--acetylneuraminic acid (X-Neu5Ac) and Fast Red Violet LB was increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
0
28
0
1
Order By: Relevance
“…BTP3-Neu5Ac was synthesized according to the procedure described previously 9 . Next, sialidase activity imaging was performed according to the procedure described previously 7,9 . Briefly, tails of pancreas were quickly harvested from C57BL/6J mice and then embedded in Tissue-Tek OCT compound (Sakura Finetechnical, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BTP3-Neu5Ac was synthesized according to the procedure described previously 9 . Next, sialidase activity imaging was performed according to the procedure described previously 7,9 . Briefly, tails of pancreas were quickly harvested from C57BL/6J mice and then embedded in Tissue-Tek OCT compound (Sakura Finetechnical, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of sialidase activity. Sialidase activity was measured according to the procedure described previously 7,41 . Briefly, INS-1D cells or C6 rat glioma cells stably expressing the rat sialidase isozyme Neu3 were lysed in n-octyl-β-D -glucoside buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an increase in sialidase activity at hippocampal plasma membranes within a few seconds was detected upon neural excitation by using rat brain slices and a histochemical imaging probe for sialidase activity 67 . This increase in sialidase activity, also shown by the increase in extracellular free sialic acids after 30 min, was linked to a change in the subcellular localization of sialidases, where they suggested that mainly Neu4 is responsible for the desialylation 67 .…”
Section: Since Protein Translocation Between the Sds-insoluble And Sdmentioning
confidence: 99%
“…Recently, an increase in sialidase activity at hippocampal plasma membranes within a few seconds was detected upon neural excitation by using rat brain slices and a histochemical imaging probe for sialidase activity 67 . This increase in sialidase activity, also shown by the increase in extracellular free sialic acids after 30 min, was linked to a change in the subcellular localization of sialidases, where they suggested that mainly Neu4 is responsible for the desialylation 67 . The increased sialidase activity was further shown to influence intracellular calcium levels and down-regulate glutamate release, thereby suggesting that sialidase functions as a negative feedback regulator upon synaptic transmission 68 .…”
Section: Since Protein Translocation Between the Sds-insoluble And Sdmentioning
confidence: 99%
“…We found that sialidase activity in the rat CA 3-layer lucidium immediately increases in response to LTP-induced high-frequency stimulation. 16,17) To elucidate the spatiotemporal dynamics of sialidase activity during LTP induction, abrupt changes in sialidase activity in response to LTP-induced high-frequency stimulation were determined using BTP3-Neu5Ac. When the hippocampal CA3 region was stained with BTP3-Neu5Ac at pH 7.3, the lamellar mucus showed relatively strong fluorescence in the CA3 region (Fig.…”
Section: Imaging Of Spatiotemporal Dynamics Of Sialidase Activity By mentioning
confidence: 99%